The effect of atrial fibrillation intervention on nocturnal respiratory events in elderly patients with persistent AF. (1st April 2019) - Eysenck, William; Sulke, Neil; Freemantle, Nick; Patel, Nikhil R.; Furniss, Steve S.; Veasey, Rick A.
Abstract: Background: Sleep‐disordered breathing (SDB) and atrial fibrillation (AF) are associated. This study investigated the impact of AF intervention on 6‐month home sleep testing data. Methods: Sixty‐seven patients (aged 66 to 86, 53% male) with persistent AF were randomized (1:1:1) to direct current cardioversion (DCCV) (22 patients), permanent pacemaker (PPM) + atrioventricular node ablation (AVNA) + DCCV (22 patients) or AF ablation (23 patients). Baseline and 6‐month multichannel home sleep tests with the Watch‐PAT200 (Itamar Medical Lts., Caesarea, Israel) were recorded. Implantable cardiac monitors (ICMs) (Medtronic Reveal XT, Minneapolis, Minnesota) in the DCCV and AF ablation groups, and PPM Holters in the 'pace and ablate' group were utilized to assess cardiac rhythm beat‐to‐beat throughout the study period. Results: The prevalence of moderate‐to‐severe SDB [apnoea‐hypopnoea index (AHI) ≥ 15/h] was 60%. At 6 months there was no change in AHI, Epworth sleepiness scale, sleep time, % REM sleep, respiratory desaturation index or central apnoeic events. Twenty‐five patients (15 AF ablation, 9 DCCV and 1 following DCCV post‐AVNA) maintained SR at 6 months confirmed on ICMs in these patients. AHI fell from 29.8 ± 26.6/h to 22.2 ± 20.4/h; P  = 0.049. Conclusions: SDB is highly prevalent in patients with persistent AF. Restoration of sinus rhythm, and the associated long‐term recovery of haemodynamics, is associated with a significant reduction in AHI. This implicates reversal of fluid shift from the lower limbs to the neck region, a key mechanism in the pathogenesis of SDB.